Pelaksanaan Pembelajaran E-Learning Berbasis Web pada Mata Pelajaran PPKn di SMK Negeri 3 Mataram - Yulia Herly Ismiati; Edy Herianto; Bagdawansyah Alqadri; M. Zubair (PALAPA, 2022)
This study aims to determine the Implementation of Web-Based E-Learning Learning in Civics Subjects at SMK N 3 Mataram. The approach used is a qualitative research approach with descriptive methods. The research subjects consisted of all PPKn subject teachers at SMKN 3 Mataram. The informants in this study were the Principal at SMKN 3 Mataram and the Deputy Head of Curriculum. The latest data collection used observation, interviews, and documentation. This study's results indicate that web-based E-learning implementation is carried out quite well-using laptops and internet networks. The positive impact of E-learning learning can add insight and increase the ability to master technology. The adverse effect of E-learning learning is the reduced interaction between teachers and students, so teachers and students need to adapt to the web-based e-learning learning model. The supporting factors for web-based E-learning are the availability of learning media and teaching materials. Another part, internet quotas and the inhibiting factors for web-based E-learning learning are limited time during the online assessment. Besides, the material delivered is too long to make students not focus. It can cause boredom, causing boredom., and a lack of student learning motivation.